EKOLOGI BERWAWASAN GENDER DALAM AL-QUR’AN: ANALISIS TEMATIK BERBASIS TAFSIR AL-MISBAHDAN AL-AZHAR - Nurhalima Nurhalima; Adelia Adelia (CV. Adiba Aisha Amira, 2025)
This research aims to explore the integration of ecological principles and gender equality within the Qur’anic ethical framework by analyzing selected verses through Tafsir Al- Misbah and Tafsir Al-Azhar. The problem addressed is the gap in understanding the Qur’anic perspective that links environmental preservation with inclusive gender participation. The study employs a thematic interpretation method (tafsir maudhu’i) combined with qualitative literature review and case studies. The results reveal that the Qur’an affirms the principles of balance (mīzān), prohibition of corruption (fasād), and equitable utilization of resources as a mandate of human stewardship (khalīfah). Furthermore, it recognizes equal contributions of men and women in righteous deeds, including environmental protection. The analysis shows that environmental degradation is not only a physical problem but also a moral, social, and structural issue, requiring inclusive cross-gender solutions. The findings contribute to expanding the maqāṣid al-sharī‘ah by incorporating ḥifẓ al-bī’ah (environmental preservation) as an essential objective, and they provide a foundation for integrating Qur’anic eco-theology and gender justice into Islamic education curricula.